Effects of breathing exercises on breathing pattern and thoracoabdominal motion after gastroplasty Efeitos de exercícios respiratórios sobre o padrão respiratório e movimento toracoabdominal após gastroplastia - Georgia Miranda Tomich; Danielle Corrêa França; Marco Túlio Costa Diniz; Raquel Rodrigues Britto; Rosana Ferreira Sampaio; Verônica Franco Parreira (Jornal Brasileiro de Pneumologia, 2010)
OBJECTIVE: To evaluate breathing pattern and thoracoabdominal motion during breathing exercises. METHODS: Twenty-four patients with class II or III obesity (18 women; 6 men) were studied on the second postoperative day after gastroplasty. The mean age was 37 ± 11 years, and the mean BMI was 44 ± 3 kg/m². Diaphragmatic breathing, incentive spirometry with a flow-oriented device and incentive spirometry with a volume-oriented device were performed in random order. Respiratory inductive plethysmography was used in order to measure respiratory variables and thoracoabdominal motion. RESULTS: Comparisons among the three exercises showed significant differences: tidal volume was higher during incentive spirometry (with the flow-oriented device or with the volume-oriented device) than during diaphragmatic breathing; the respiratory rate was lower during incentive spirometry with the volume-oriented device than during incentive spirometry with the flow-oriented device; and minute ventilation was higher during incentive spirometry (with the flow-oriented device or with the volume-oriented device) than during diaphragmatic breathing. Rib cage motion did not vary during breathing exercises, although there was an increase in thoracoabdominal asynchrony, especially during incentive spirometry with the flow-oriented device. CONCLUSIONS: Among the breathing exercises evaluated, incentive spirometry with the volume-oriented device provided the best results, because it allowed slower, deeper inhalation. OBJETIVO: Avaliar o padrão respiratório e o movimento toracoabdominal durante exercícios respiratórios. MÉTODOS: Vinte e quatro pacientes com obesidade de nível II e III (18 mulheres; 6 homens) foram estudados no segundo dia pós-operatório após gastroplastia. A média de idade era de 37 ± 11 anos, e a média de IMC era de 44 ± 3 kg/m². Exercício diafragmático, espirometria de incentivo orientada a fluxo e espirometria de incentivo orientada a volume foram realizados em ordem aleatória. A pletismografia respiratória indutiva foi utilizada para avaliar variáveis do padrão respiratório e do movimento toracoabdominal. RESULTADOS: As comparações entre os exercícios demonstraram diferenças significativas: maior volume corrente durante a espirometria de incentivo orientada a fluxo ou orientada a volume (vs. exercício diafragmático), menor frequência respiratória durante a espirometria de incentivo orientada a volume (vs. espirometria de incentivo orientada a fluxo), e maior ventilação minuto durante a espirometria de incentivo orientada a fluxo ou orientada a volume (vs. exercício diafragmático). O movimento toracoabdominal não foi modificado durante os exercícios respiratórios e houve um aumento na assincronia toracoabdominal, especialmente durante a espirometria de incentivo orientada a fluxo. CONCLUSÕES: Entre os exercícios respiratórios avaliados, a espirometria de incentivo orientado a volume forneceu os melhores resultados, pois possibilitou uma inspiração mais lenta e profunda.